EVALUASI TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 4.1 DOMAIN DS ME DI DINAS PEKERJAAN UMUM PROVINSI GORONTALO - Rahmat Kobie; Rampi Yusuf; Rochmad Mohammad Thohir Jassin (Diffusion: Journal of Systems and Information Technology, 2021)
Abstract The Public Works Service of Gorontalo Province still confronts a problem, i.e., unavailability of the evaluation of maturity level measurement of information technology performance. Thus, its loss towards the development of information technology information in the aforementioned provincial service will be slow. This present study aimed to find out the maturity level of information technology performance and to provide a recommendation in terms of performance betterment to improve information technology performance in the Public Works Service of Gorontalo Province. Cobit 4.1 Framework was used on account of its function as a supporting tool featuring the most appropriate scope of discussion from the aspect of research needs. One of which was to measure the performance of service delivery to be more beneficial in information technology management by applying DS (Delivery and Support) and ME (Monitoring Evaluation) domains. It was indicated that the performance maturity level in the site area had not arrived at the expected value. For such reasons, it was expected that the evaluation of information technology performance measurement could serve as the source of information. This research suggested the provincial service to enhance its information technology performance. Keywords: Governance Evalution; Information Technology Performance; Cobit 4.1 Framework; DS and ME Domains.